Analisis Pelaksanaan Perceraian di Depan Sidang Pengadilan Agama Perspektif Ma’anil Hadis - Moh. Rafi Irvanul Vaza (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2024)
Divorce is an emergency exit from continuous family conflict. Islam permits divorce but is hated by Allah swt for reasons prohibited by Islamic law. The reality in the community is that there is an incomplete understanding because of the disparity between the provisions of positive law and the hadith that divorce is granted even in jest or in a serious situation and without intention. The position of the court in organising the administration of marriage is very important. The purpose of this study is to examine and analyse the hadith of divorce even in jest or in seriousness and without intention whether it can be used as a basis or is no longer relevant. This research uses a qualitative descriptive approach. Data collection in this research is through literature study. Meanwhile, the data analysis is carried out by examination, classification, verification, analysis and conclusion. The result of the study is that the hadith of the fall of divorce even in jest or in a serious situation and without intention can be used as a basis and as a warning to everyone to be careful in guarding the tongue, especially the issue of divorce. If contextualised with the lives of people in Indonesia, divorce not in front of the court cannot guarantee that it can avoid negative things, especially the fate of women and children after divorce, considering that there are benefits that will be obtained if the divorce is carried out in front of a court session.